Comparison of multiple mycotoxins in harvested maize samples in three years (2018–2020) in four continents. Issue 3 (4th March 2022) - Raj, Jog; Farkaš, Hunor; Jakovčević, Zdenka; Medina, Angel; Magan, Naresh; Čepela, Robert; Vasiljević, Marko
ABSTRACT: This study has examined the pattern of mycotoxin contamination of maize destined for animal feed in different global regions over a period of 3 years (2018–2020) with up to 1000+ samples analysed in each year. Overall, >75% of samples in each of the survey years were contaminated with multiple mycotoxins regardless of the global region (Europe, Africa, Asia, South Americas countries). Using LC-MS/MS, it was possible to quantify the relative contamination present in the samples in each year from the different regions of eight different mycotoxins including aflatoxin B1 (AFB1 ), ochratoxin A (OTA) deoxynivalenol (DON), fumonisin B1 (FB1 ) and B2, zearalenone (ZEA), T-2 and HT-2 toxins. The trends in mycotoxin contamination showed that there was a consistent contamination with DON in the 3 sampling years in all four regions. Interestingly, AFB1 contamination was prevalent in all regions in 2018, but more predominant in Europe and in 2019. In contrast, in 2020 it was found to be the major contaminant in Africa only. However, FB1 contamination of maize which was prevalent in Europe in 2018, became more prevalent in Asia and LATAM countries in 2019 and even in African maize in 2020. Comparisons of contamination with different mycotoxins in each of the years globally showed significant differences for AFB1, FB1, DON and ZEA between the different years. These results are discussed in relation to the trends of contamination of maize with mixtures of mycotoxins and the implication for their control in this key commodity used as an important ingredient in animal feed.